URETHROVAGINAL FISTULA: A RARE COMPLICATION SECONDARY TO IMPACTED FOREIGN BODY IN VAGINA - Jalil, Aisha; Hayat, Zartaj; Farouk, Khalid; Akhtar, Nosheen (Journal of Ayub Medical College Abbottabad, 2019)
We report a case of urethrovaginal fistula following impacted foreign body in vagina. Fistula was suspected on the basis of history and examination and was later on confirmed by voiding cystourethrogram. Cystourethroscopy was done and the fistula was repaired transvaginally in layers. We are reporting this case because of its rarity Keywords: Urethrovaginal fistula; impacted foreign body; voiding cystourethrogram